Rancang Bangun Media Pembelajaran Interaktif Berbasis Articulate Storyline pada Mata Pelajaran Dasar-Dasar Kejuruan Kelas X di SMK Negeri 1 Sumatera Barat - Nigel Mahardhika; Sartika Anori (Lembaga Yasin AlSys, 2025)
This study is motivated by the low level of understanding and learning outcomes among Grade X students in the Audio Video Engineering program at SMK Negeri 1 West Sumatra in the subject of Dasar-Dasar Kejuruan (DDK), which is attributed to the limited use of engaging and student-appropriate interactive learning media. The aim of this research is to develop a valid and practical interactive learning media based on Articulate Storyline for use in DDK learning. The method employed is Research and Development (R&D) using the 4-D development model (Define, Design, Develop, Disseminate), limited to the Develop stage. Data were collected through observation, validation questionnaires from subject matter and media experts, and practicality testing by students. The results indicate that the developed media received very high validity scores from media experts (86.87%) and subject matter experts (94.12%). In addition, a practicality test involving 15 students showed a very high level of practicality, with an average score of 89.77%. The study concludes that the interactive learning media based on Articulate Storyline meets the criteria for validity and practicality and is feasible for use as a supporting tool to enhance the quality of DDK learning in vocational schools.